The state of readiness to professional self-educational activity among rural school teachers - Коростіль, Лідія (Pedagogy of Higher and Secondary Education, 2014)
Korostil L. А. The state of readiness to professional self-educational activity among rural school teachers. The article deals with the features of self-education of rural school teachers. The results of self-diagnostics aimed to determine the state of readiness of teachers of different age groups to self-educational activity are highlighted in the article. A comparison was made and it was proved that in practice teacher’s capacity for self-educational activity not only develops and deepens, but also fades and changes directions. It happens due to age-related changes in human capabilities and interests, as well as teacher’s professional burnout.